Recent Publications (Quarterly Journal of Economics, 1957)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 71, Issue 2, May 1957, Pages 325–327, https://doi.org/10.1093/qje/71.2.325 Published: 01 May 1957